Anatomical Basis and Clinical Research of Pelvic Autonomic Nerve Preservation with Laparoscopic Radical Resection for Rectal Cancer - 刘彦 卢晓明 陶凯雄 马建华 蔡开琳 王琳芳 牛彦峰 王国斌 (Journal of Huazhong University of Science and Technology. Medical sciences, 2016)
The clinical effect of laparoscopic rectal cancer curative excision with pelvic autonomic nerve preservation（PANP） was investigated. This study evaluated the frequency of urinary and sexual dysfunction of 149 male patients with middle and low rectal cancer who underwent laparoscopic or open total mesorectal excision with pelvic autonomic nerve preservation（PANP） from March 2011 to March 2013. Eighty-four patients were subjected to laparoscopic surgery, and 65 to open surgery respectively. The patients were followed up for 12 months, interviewed, and administered a standardized questionnaire about postoperative functional outcomes and quality of life. In the laparoscopic group, 13 patients（18.37%） presented transitory postoperative urinary dysfunction, and were medically treated. So did 12 patients（21.82%） in open group. Sexual desire was maintained by 52.86%, un-ability to engage in intercourse by 47.15%, and un-ability to achieve orgasm and ejaculation by 34.29% of the patients in the laparoscopic group. Sexual desire was maintained by 56.36%, un-ability to engage in intercourse by 43.63%, and un-ability to achieve orgasm and ejaculation by 33.73% of the patients in the open group. No significant differences in urinary and sexual dysfunction between the laparoscopic and open rectal resection groups were observed（P〉0.05）. It was concluded that laparoscopic rectal cancer radical excision with PANP did not aggravate or improve sexual and urinary dysfunction.